The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

Computer-Based Generation of Learner-Sensitive Feedback to Argumentative Learner Texts - Kilsbach, Sebastian; Michel, Nadine (Proceedings of the Tenth Conference of the International Society for the Study of Argumentation)
What is learner-sensitive feedback to argumentative learner texts when it is to be issued computer- based? Learning stages are difficult to quantify. The paper provides insight into the history of research since the 1980s and a preview of what this automated feedback might look like. These questions are embedded in a research project at the Universities of Paderborn and Hannover, Germany, from which a software (project name ArgSchool) emerges that will provide such feedback.
Keywords: AI; argumentation mining; discourse history; (automated; learner-sensitive) feedback

Überlieferungs-Chance und Überlieferungs-Zufall frühneuzeitlicher Bibliotheksbestände. Fortführung eines Gesprächs - Süßmann, Johannes (Die Sicht auf das Gestern mit den Augen von heute. Festschrift für Jörg W. Busch zum 65. Geburtstag)
Keywords: Early Modern History; History of Libraries; Tradition of Libraries

"Contributing means investing in Spain" – Media campaigns on tax education in Spain after the transition to democracy - Schönhärl, Korinna (Themenportal Europäische Geschichte)
What can the tax authorities do to encourage citizens to pay their taxes more honestly? They can promote honest tax payments in the media! Such tax education, which is completely unfamiliar to German taxpayers, can look back on a long tradition in the USA, for example, and other countries. It has also been practised in Spain since the end of the 1960s and intensified after the transition to democracy. A Treasury television advertisement from 1990 allows an analysis of the narratives used by tax education in the young Spanish democracy. The intense and difficult struggle by state institutions for democratic, equal rights for all citizens even 15 years after Franco's death becomes obvious.
Keywords: Spanish History; Financial History; Tax History; Video as historical sources

Digitalisierung und Umwelt – eine verflochtene Digitalgeschichte der Gegenwart im Angesicht des Klimawandels - Schmitt, Martin
Keywords: Digitalisierung; Digitalgeschichte; Umweltgeschichte; Anthropozän; Computer; Rechenzentrum; Digital History

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Zwischen Dethematisierung und Demonetarisierung Der Holocaust in Darstellungen von NS und Zweitem Weltkrieg auf YouTube - Quast, Julia (Zeitschrift für Genozidforschung)
Between Dethematizing and Demonetisation: The Holocaust in depictions of National-Socialism and World War Two on YouTube – In September 2018, an ambitious and highly noteworthy project for the construction and distribution of a broad-reaching portrayal of 20th-century violence in the digital age was launched: the YouTube channel World War Two (WW2). Their mission was to present the experiences of those who lived through the war in a radically objective, apolitical, and detailed manner. The main series, sharing the same title as the channel, focused on military events, while another series titled War Against Humanity (WAH) would address war crimes, human rights abuses, the mass murder of civilians and prisoners of war, Nazi euthanasia crimes, and the Holocaust. This division of the narrative into a military history (main series) and a separate history of war crimes and the Holocaust (side series) raises important questions about the conditions, opportunities, and limitations that YouTube’s media and economic structures impose on the portrayal of war, mass violence, and genocide. The paper also examines how these structures influence the narrative and shape the presented historical image, and what consequences arise for the depiction of war and history from an academic perspective. Lastly, it explores the reasons behind this narrative split: whether it was a deliberate decision to systematically differentiate the storytelling or a strategic move shaped by YouTube’s media and economic constraints. The question arises: to what extent can historical education on digital platforms like YouTube, driven by the need for content monetization, still align closely with academic standards?
Keywords: Zweiter Weltkrieg; Holocaust; Geschichtsbild; Public History; Social Media; YouTube; Erinnerungskultur

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

Tax Morale and the Church: How Catholic Clergies Adapted Norms of Paying Taxes to Secular Institutions (1940s–1950s) - Schönhärl, Korinna (Reassessing the Moral Economy Religion and Economic Ethics from Ancient Greece to the 20th Century)
Paying taxes is a field of economic activity that has always been highly morally charged: the question of who pays how much or can avoid or evade the prescribed payments is always closely related to debate about a fair societal distribution of burdens. In the process of moralisation, therefore, faith communities such as the Catholic Church also repeatedly seized the floor to propagate certain norms. The article examines the contributions of theologians from Spain, the USA and West Germany in the 1940s and 1950s. It concludes that the norms of taxation they propagated differed greatly depending on the institutional and economic frameworks within which they operated. The analysis proves taxation to be a field of economic action and societal dispute where economics and morality are indissolubly interconnected.
Keywords: Tax history; religious history: financial history; catholic church; history of economic thought

Will do? Causes and volitions - Wells, Aaron (Metascience)
Keywords: History and Philosophy of Science; General Social Sciences; History

Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

DaF und DaZ im Kontext Deutsch für den Beruf: Schnittstellen und Divergenzen - Niederhaus, Constanze; Prikoszovits, Matthias (Deutsch als Fremdsprache)
Keywords: Computer Science Applications; History; Education

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

Science and the Principle of Sufficient Reason: Du Châtelet contra Wolff - Wells, Aaron (HOPOS: The Journal of the International Society for the History of Philosophy of Science)
Keywords: History and Philosophy of Science

Editorial: Netzwerke und Vernetzung im Sport - Meier, Heiko; Kukuk, Marc; Riedl, Lars (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Technological Expectations and the Making of Europe - Hälterlein, Jens (Science & Technology Studies)
In a case study approach, the paper traces how technological expectations have been influential in the creation of European institutions, R&D programmes and regulatory instruments and how they have contributed to processes of European integration. The first case study shows how the promises of a coming ‘Atomic Age’ have been mobilized to support the foundation of the European Atomic Energy Community and, thus, contributed to European integration in the post-WW2 era. The second case study analyses how the security stream within the EU’s framework programmes for R&D is shaped by the promise of ‘technosecurity’ and enacts the normative claim of the EU’s security integration in the post-Cold War era. The third case study analyses how the EU’s AI strategy and AI act articulates the vision of a ‘human-centric AI’ and how this vision is related to the EU’s current attempt to restore citizens’ trust in times of crisis.
Keywords: History and Philosophy of Science

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne Philosophy and Science in the Age of Émilie Du Châtelet (1706-1749))
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz